Effects of virgin microplastics on goldfish (Carassius auratus). (December 2018) - Jabeen, Khalida; Li, Bowen; Chen, Qiqing; Su, Lei; Wu, Chenxi; Hollert, Henner; Shi, Huahong
Abstract: Microplastics (MPs) are abundant in freshwater and marine environments. They are diverse shape and size and are ingested by organisms. In this study, goldfish ( Carassius auratus ) were exposed via diet to three types of virgin MPs material types and shapes including fibers, fragments, and pellets. After six weeks of exposure, various sub-lethal effects, but no mortality, was observed. Fish exposed to plastic showed significant weight loss compared with the control. Fibers were found in the gills, gastrointestinal tract (GIT), and feces were not likely to accumulate in the GIT. Pronounced and severe alterations were found in the livers of fish exposed to fibers. The distal intestine showed more pronounced and severe changes compared to the proximal intestine, likely due to an intake of fibers. The ingestion of fibers caused the highest frequencies of progressive and inflammatory changes in the livers and intestines. This is in accordance with the higher organ index in these organs compared to other texa. Conversely, fragments and pellets were not ingested but chewed and expelled. Chewing process resulted in damages to the jaws as ranging from slight exfoliation to deep incisions. The highest frequency of regressive and circulatory (e.g., dilated sinusoids) changes was found in fish exposed to fragments, specifically in the upper and lower jaw, and in lower jaw and liver, respectively. Together, these results demonstrate that ingestion and chewing of MPs lead to damages in various organs and tissues of the gastrointestinal system, and suggest that different materials can have drastically different impacts on fish. Graphical abstract: Highlights: Ingestion and effects of MPs in fish are largely dependent on their shape and size. Only fiber-based food was ingested but fragment and pellet-based were expelled. Fibers were found in the gills, gastrointestinal tract, and feces. Pronounced and severe damages were found in the liver of the fiber-based group. Severe damage in the jaws was observed in fragment-based group due to chewing.